Pengaruh Kompetisi, Pertumbuhan Laba dan Kinerja Lingkungan terhadap Pengungkapan Informasi Emisi Karbon pada Perusahaan - Hilmi Hilmi; Lilis Puspitawati; Ranti Utari (Politeknik Ganesha Medan, 2020)
Disclosure of carbon emissions (Carbon Emission Disclosure) is a voluntary disclosure of carbon emissions resulting from the company's production process. This research itself aims to obtain empirical evidence about competition, profit growth and environmental performance on the disclosure of carbon emissions of manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2018 period. The method applied to measure the extent of disclosure of carbon emissions adopted from the check list developed based on the request sheet obtained from the Carbon Disclosure Project (CDP). The results of this study indicate that competition, profit growth and environmental performance have no effect on Carbon Emission Disclosure.